Theater of objects and consumer society (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
In this article we present a series of reflections, written with four hands, addressing the insertion of the real object in the performing arts, as a phenomenon of the development of the consumer society and other historical factors that occurred throughout the 20th century. The greatest emphasis is given to the theater of objects, a movement that was developed between the 1970s and 1980s. In it, the transgression of traditional concepts of the animation theater is observed, in addition to the mere functionalism of objects, transforming them into metaphors of the human condition itself and questioning its condition as a commodity in capitalist society.
Keywords: Objects; Consumer society; Merchandise; Theater; Theater of objects